1997
DOI: 10.1046/j.1365-2621.1997.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of Lactobacillus casei inoculum, modified atmosphere packaging and storage temperature in controlling Aeromonas hydrophila in ready‐to‐use vegetables

Abstract: Carbon dioxide concentration, Lactobacillus casei inoculum size and storage temperature were varied according to a Central Composite Design in order to assess the effects of these variables and their interactions on the growth of Aeromonas hydrophila and lactic acid bacteria in ready‐to‐use mixed salad vegetables packaged under modified atmosphere. The growth curve parameters, modelled according to the Gompertz equation, were analysed to generate polynomial equations. The model obtained emphasized the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…(2001). Our study was in agreement with the positive effect of the atmospheric conditions containing reduced oxygen and 10% CO 2 on L. rhamnosus growth as it was reported previously by Vescovo et al . (1997) and Reuter (1985).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…(2001). Our study was in agreement with the positive effect of the atmospheric conditions containing reduced oxygen and 10% CO 2 on L. rhamnosus growth as it was reported previously by Vescovo et al . (1997) and Reuter (1985).…”
Section: Resultssupporting
confidence: 94%
“…A positive effect of microaerophilic environment on growth performance as measured by OD was also observed by Pandrangi and LaBorde (2004) and Talwalkar et al (2001). Our study was in agreement with the positive effect of the atmospheric conditions containing reduced oxygen and 10% CO 2 on L. rhamnosus growth as it was reported previously by Vescovo et al (1997) and Reuter (1985). The general purpose of this experiment was to decrease the riboflavin assay time.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, various studies have proposed the use of microbial interaction combined with MAP and low storage temperatures to reduce the survival and/or growth of Aeromonas spp. Vescovo et al (1997) investigated the combined effect of Lactobacillus casei inoculums, MAP and chilled temperature on the growth and survival of A. hydrophila in ready-to-use vegetables. Their findings suggested that L. casei inoculums size was the main factor that influenced the kinetic parameters of A. hydrophila, while CO 2 concentration in the package extended the lag phase of A. hydrophila.…”
Section: Aeromonas Sppmentioning
confidence: 99%
“…Lewus, Kaiser, and Montville (1991) reported on the opportunity for inhibition of two A. hydrophila strains by bacteriocin-producing lactic acid bacteria, isolated from retail cuts of meat. Vescoto, Scolari, Orsi, Sinigaglia, and Torriani (1997) reported that combinations of carbon dioxide, Lactobacillus casei and low storage temperature can reduce A. hydrophila survival in ready-to-use mixed salad vegetables. Santos, Lopez-Diaz, Garcia-Fernandez, Garcia-Lopez, and Otero (1996) proved that Lactococcus lactis subsp.…”
Section: Prevention and Controlmentioning
confidence: 99%